HUMANIZATION OF THE CRIMINAL-EXECUTIVE SYSTEM - Рудник, Т. В. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2007)
In this article the author examines the principle of humanism in the criminal executive law of the problem of implementation of this principle in the execution and serving of sentences in the form of imprisonment and treatment of convicts and offers ways to solve them.